The Role of Financial Statements Customers in Credit Granting Decisions Small Business Capital PT. Bank Bengkulu Panorama Market Sub-branch (Indonesian) - Nevi Fitriani (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2026)
In providing credit, several relevant information is needed and has a very large role for banks in their efforts to distribute and secure credit, namely in the form of financial reports of debtor companies. With these financial reports, the bank will know the progress and decline of the company in one period, namely by conducting an analysis of balance sheet items and profit and loss statements. The formulation of the problem in this study is how the role of customer financial reports in the decision to provide small business capital credit at PT. Bank Bengkulu Pasar Panorama Branch and the aim is to determine the role of customer financial reports in the decision to provide working capital credit at PT. Bank Bengkulu Pasar Panorama Branch. This type of research uses quantitative methods or quantitative descriptive studies. Data were collected through observation and documentation and analyzed with financial ratios of solvency, liquidity and profitability for a 3-year period from 2009 - 2011, namely for the Sinar Jaya store and the Nissa store. The results of the study concluded that financial reports play a very important role in the decision to provide small business capital credit at PT. Bank Bengkulu Pasar Panorama Branch, because from the financial reports it can be seen that the prospective debtor company has a fairly good financial ratio. The financial ratios used by PT Bank Bengkulu to assess prospective borrowers are the debt-to-total-assets ratio, DER, cash ratio, gross profit margin, and net profit margin. These include ROA and ROE, but these ratios were not examined. Based on the ratios analyzed by the researcher, Toko Nisa and Sinar Jaya are eligible for working capital loans because these five ratios meet or exceed the standards set by PT Bank Bengkulu.